The Type of Dormancy and Pre Treatment for Breaking Dormancy of Balsa (Ochroma bicolor ROWLEE) Seed - Muhammad Zanzibar (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2017)
One of the determinants of the success of germination is when the dormancy inhibiting factor in the seed has been controlled. When experiencing dormancy symptoms then before germination need to do preliminary treatment. This study aims to determine the type of dormancy and pretreatment for breaking the dormancy of balsa seeds.The experimental design used was a complete randomized design (RAL). The observed variables were germination capacity (GC), mean days germination (MDG) and germination value es (GV). The preliminary treatment used included the use of 80 oC hot water, the use of water with room temperature 27 oC, giberalin acid (GA3), hydrogen peroxide (H2O2), and without treatment (control). The results show that the dormant type of balsa seed is a combination of external dormancy (skin hardness) and internal dormancy (embryo). The best preliminary treatment was obtained on soaking the seeds in GA3 (75 ppm) for 24 hours.